1995
DOI: 10.1002/elps.11501601183
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional polyacrylamide gel electrophoresis with immobilized pH gradients in the first dimensin (IPG‐Dalt): The state of the art and the controversy of vertical versus horizontal systems

Abstract: After having established the basic protocol of two-dimensional electrophoresis with immobilized pH gradients in the first dimension (IPG-Dalt) in 1988 (A. Görg et al., Electrophoresis 1988, 9, 531-546), some critical parameters of the actual IPG-Dalt protocols as well as the results obtained with horizontal and vertical second-dimensional sodium dodecyl sulfate-electrophoresis are demonstrated and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(140 citation statements)
references
References 25 publications
(14 reference statements)
1
135
0
3
Order By: Relevance
“…This was found to improve IEF and voltage could be increased up to 5000V. This is in line with the concept of electrophoretic desalting described by Gorg et al (1995) in which samples with high salt concentration were directly desalted in the IPG strip using a low voltage during the first few hours of IEF. Davidsson et al (2002) also previously reported that such prolonging of IEF run could improve the problem of incomplete focusing due to the presence of ampholytes in cerebrospinal fluid samples.…”
Section: Wwwintechopencomsupporting
confidence: 83%
“…This was found to improve IEF and voltage could be increased up to 5000V. This is in line with the concept of electrophoretic desalting described by Gorg et al (1995) in which samples with high salt concentration were directly desalted in the IPG strip using a low voltage during the first few hours of IEF. Davidsson et al (2002) also previously reported that such prolonging of IEF run could improve the problem of incomplete focusing due to the presence of ampholytes in cerebrospinal fluid samples.…”
Section: Wwwintechopencomsupporting
confidence: 83%
“…Final purification of the Mbs or globin chains was performed by semipreparative isoelectric focusing on immobilized pH gradient gel strips (pH 3-10) under native or denaturing conditions (32). Pe Mb was dissolved in 0.2% ampholytes (pH 4 -10) while Ih Mb was dissolved and run in 9 M urea, 1% dithiothreitol, 2% CHAPS, 1 0.8% ampholytes (pH 3-10).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting polypeptide chain was denatured by heating in 6 M guanidine HCl, 1% 2-mercaptoethanol, 50 mM Tris-HCl, pH 7.0, at 100°C for 3 min and subjected to RP-HPLC on a Vydac C 4 column (4.1 mm) developed in a 0.1% trifluoroacetic acid/acetonitrile system. Purity of the obtained Mb and globin fractions was analyzed by one-(SDS-PAGE) and two-dimensional electrophoresis (32,33).…”
Section: Methodsmentioning
confidence: 99%
“…These pH gradients were often in the form of tube gels with carrier ampholytes. The introduction of chemistries (17) to immobilize the pH gradient into the gel matrix and the construction of the gel on a solid backing (18,19) was a significant step in making IEF accessible to more than a handful of researchers. Most current applications of IEF use these immobilized gradients in some sort of dedicated instrument that controls both gel current and temperature (20).…”
Section: Electrophoresic Separation Methodsmentioning
confidence: 99%